1994
DOI: 10.1080/00071669408417707
|View full text |Cite
|
Sign up to set email alerts
|

Plasma alpha 1‐acid glycoprotein concentration in broilers: Influence of age, sex and injection ofescherichia colilipopolysaccharide

Abstract: 1. The influence of age, sex and injection of Escherichia coli lipopolysaccharide (LPS) on the plasma concentration of alpha-1 acid glycoprotein (AGP) was determined in broilers using the single radial immunodiffusion method. 2. Plasma AGP concentration increased in the 3 d after hatching, and then stabilised at 240 +/- 33 micrograms/ml up to 14 d of age. 3. No sex-related differences in plasma AGP concentration were observed up to 6 weeks of age. 4. A single injection of 900 micrograms LPS per chick resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 15 publications
1
26
1
Order By: Relevance
“…Cer and ␣ 1 AG concentrations were increased (Fig. 5, A and B); these changes being similar to those seen after LPS injection (13)(14)(15). ChTL1A fusion protein and GST preparations did not contain detectable levels of LPS (Ͻ100 ng/mg protein) using an Endospecy ES-50M kit (Seikagaku).…”
Section: Responsiveness To Lps Of Plasma Chtl1a Protein Levelsmentioning
confidence: 53%
See 1 more Smart Citation
“…Cer and ␣ 1 AG concentrations were increased (Fig. 5, A and B); these changes being similar to those seen after LPS injection (13)(14)(15). ChTL1A fusion protein and GST preparations did not contain detectable levels of LPS (Ͻ100 ng/mg protein) using an Endospecy ES-50M kit (Seikagaku).…”
Section: Responsiveness To Lps Of Plasma Chtl1a Protein Levelsmentioning
confidence: 53%
“…Thus, proinflammatory cytokines are also important regulators of metabolic responses in the acute phase of inflammation. In chickens, ␣ 1 AG, Cer, and NO are acute phase substances released following LPS injection (13,14,25). Our results demonstrate that ChTL1A promotes inflammation by raising these.…”
Section: The Importance Of Chtl1a In Inflammationmentioning
confidence: 54%
“…In chickens, Takahashi et al (1994) reported first that the injection of E. coli lipopolysaccharide induced an increase in plasma a'-AG level. Nakamura et al (1995) reported that IB virus and infectious laryngotracheitis virus caused an elevation of serum a'-AG levels.…”
Section: Discussionmentioning
confidence: 99%
“…'Chicken a'-AG plates' (Saikin Kagaku Institute Co Ltd, Sendai, Japan), incorporating the specific anti-chicken a'-AG serum of rabbit origin in agarose gel, were used for measurement of chicken a'-AG (Nakamura et al, 1995;Takahashi et al, 1994). This is a single radial immunodiffusion method.…”
Section: Biochemistrymentioning
confidence: 99%
“…Altered health status of birds often results in measurable changes in blood biochemistry (Hurwitz and Griminger 1961;Okumura and Tasaki 1969), measuring plasma levels of certain acute-phase proteins (Kushner and Mackiewiez 1987;Singh 1988;Saini and Webert 1991;Takahashi et al 1994;Tohyo et al 1995Tohyo et al , 1996, including the SAA protein also (Chamanza et al 1999;Gruys et al 2005), could be useful in monitoring poultry health. It has been suggested that increased circulating proteolytic cleavage of SAA may potentially contribute to the development of AA amyloid deposition (Migita et al 1996).…”
Section: Introductionmentioning
confidence: 99%